Legal Aspects of Sharing Economy Business Model - Iswandi, Andi (Jurnal Cita Hukum, 2023)
The swift advancement of the sharing economy has introduced novel issues in company regulation and equity, particularly in a Muslim-majority nation such as Indonesia. The Qur'an establishes a framework of principles, including justice, transparency, and cooperation, pertinent to contemporary business activities. This study aims to uncover legal concepts in the Qur'an applicable to the sharing economy and to explore how Indonesian rules may be modified to accord with these principles. The employed study methodology is qualitative, incorporating a literature review that utilises primary sources from the Qur'an and Islamic law, alongside a normative legal framework to examine legislation pertinent to the sharing economy sector in Indonesia. The study's findings suggest that adopting the sharing economy business model aligns with Qur'anic principles, including equitable profit distribution, the prevention of exploitation and uncertainty (gharar), and the significance of accountability and responsibility in commerce. In summary, implementing legal principles derived from the Qur'anic perspective can facilitate the establishment of equitable and transparent regulations that promote the development of the sharing economy while fostering social welfare and confidence among business entities and consumers. This study underscores the necessity of aligning contemporary rules with sharia principles to establish a just, sustainable, and Qur'anic business environment.